Distribución directa a las personas de la renta hidrocarburífera: Impactos macroeconómicos - Juan Antonio Morales (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2008)
– Bolivia has enjoyed in the past four years the effects of the bonanza in international markets for its commodity exports, mainly hydrocarbons. The policy question is then how to intertemporally maximize (and internalize) the benefits of this good fortune. The central proposition is that distributing directly to the population the rents of the hydrocarbons produces the welfare gain of higher sustainable consumption of the households because it minimizes rent-seeking and, also, because it improves the distribution of income with its attendant positive effects on long-term rate of growth of the economy. I argue that the direct distribution of the rents will not have any deleterious effect on the work or investment efforts of the private sector. However, it could mean a lower provision of public investments. The paper tries to identify the effects on growth and macroeconomic stability between distributing the hydrocarbons rents directly and using it in public investments.
Keywords: 330